2022
DOI: 10.1080/14724049.2022.2091581
|View full text |Cite
|
Sign up to set email alerts
|

Memorable nature-based tourism experience, place attachment and tourists’ environmentally responsible behaviour

Abstract: During the COVID-19 pandemic, there has been an increased emphasis on domestic travel and forms of sustainable tourism, such as nature-based tourism, due to social distancing and travelrelated safety measures. This study tests a new model for memorable nature-based tourism experiences by examining the effects of novelty, experiencescape, experience co-creation, experience intensification and satisfaction. The study also examines the relationship between memorable nature-based tourism experiences, place attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 109 publications
2
26
1
1
Order By: Relevance
“…Taken together, these results suggest that guests who take photographs during their stay in a USH intensify their experiences and have a more satisfying and memorable experience. These findings correspond to previous studies indicating that photos contribute to satisfaction (Chen et al, 2023;Li et al, 2023aLi et al, , 2023b and can elicit strong positive memories of trip experiences (Sthapit et al, 2022).…”
Section: Constructssupporting
confidence: 92%
“…Taken together, these results suggest that guests who take photographs during their stay in a USH intensify their experiences and have a more satisfying and memorable experience. These findings correspond to previous studies indicating that photos contribute to satisfaction (Chen et al, 2023;Li et al, 2023aLi et al, , 2023b and can elicit strong positive memories of trip experiences (Sthapit et al, 2022).…”
Section: Constructssupporting
confidence: 92%
“…Tourists with a high sense of place attachment will not only enjoy the scenic area more, but will also pay more attention to the sustainable development of the scenic resources and be keen to maintain the initial appearance of the area (Bricker & Kerstetter, 2000). At the same time, previous studies have shown that scholars generally agree that place attachment is an important predictor of environmentally responsible behavior (Jia & Lin, 2015;Li et al, 2020;Sthapit et al, 2022). Jia believes that when visitors have a high level of attachment to the environment, they gradually develop a commitment to environmental protection and are more inclined to take the initiative to implement environmentally responsible behavior.…”
Section: Organism-responsementioning
confidence: 98%
“…When tourists are deeply impressed or highly familiar with the travel experiences of a certain destination, that valuable and unforgettable experiences will stimulate their various emotions toward the destination, and the resulting strong feelings will make them more attached to the destination (Tsai, 2016;Sthapit et al, 2022b). Previous studies have confirmed that memory makes an important component of destination attachment (Sthapit et al, 2018(Sthapit et al, , 2022aCifci, 2022). Therefore, tourists have a long-term memory of a destination, they will have a strong feeling toward the destination, and which makes them have an attachment to the destination.…”
Section: Destination Attachmentmentioning
confidence: 99%